The Glycine-Rich Domain Protein GRDP2 Regulates Ovule Development via the Auxin Pathway in Arabidopsis - Wang, Lulu; Liu, Yanhui; Aslam, Mohammad; Jakada, Bello Hassan; Qin, Yuan; Cai, Hanyang (Frontiers in Plant Science, 2021)
The glycine-rich domain proteins (GRDP) have been functionally implicated in the cell wall structure, biotic and abiotic stress responses. However, little is known about GRDP genes in female gametophyte development of Arabidopsis. This study shows that GRDP2, a glycine-rich domain protein, plays a crucial role in female gametophyte development. In GRDP2 overexpression lines, grdp2-3, the embryo sacs were arrested at FG1 and no nucleus stages. Furthermore, callose staining shows that cell plate formation during megasporogenesis is disturbed in grdp2-3. In contrast, the pollen development is not affected in grdp2-3. The expression patterns of auxin-specific marker lines in female gametophyte showed that the auxin distribution and transport were significantly changed during megagametogenesis in grdp2-3. In addition, compared with the membrane-localized pattern of PIN1, PIN2, and PIN7 in WT, the signals were detected in the cytoplasm in grdp2-3. Together, our data suggest that GRDP2 plays an essential role in auxin-mediated female gametophyte development.